Climate Change and Institutional Resilience in Arctic Environmental Governance - Stokke, Olav Schram (Politics and Governance, 2023)
This article highlights recent successes and failures in efforts to manage Arctic marine living resources to improve our understanding of institutional resilience—that is, the ability of cooperative institutions to maintain their performance despite severe disruptions to their operating environments. Rising ocean temperatures and other impacts of climate change may alter the spatial distribution of fish stocks, including their relative attachment to exclusive economic zones and their availability on the high seas. As evident in the examined Arctic cases, which involve the world’s largest stocks of cod, herring and mackerel, such changes may complicate core resource management tasks, including the regulatory task of reaching an agreement among user states on quotas and other restraints that align with scientific advice. The cross-case variance in regulatory resilience to climate-related and other changes in cooperative circumstances sheds light on general propositions regarding the drivers and inhibitors of institutional resilience, including institutional characteristics and the severity of the political challenges posed by changing circumstances.